Processos cognitivos que operam na construção da referência: uma análise das produções textuais elaboradas na EaD - UFRN - Diniz, Emanuelle Pereira de Lima (2012)
Beneath the theoretical assumptions of Cognitive Linguistics contemporary, we analyze the cognitive processes underlying the construction of the reference in the text. To do so, we choose as corpus the written textual productions of undergraduates at the Department of Distance Education/UFRN provided in sections of responses of presential evaluation activities and activities in the Moodle virtual ambience. These activities and texts were produced in the discipline of Reading, Interpretation and Textual Production taught in the courses of Chemistry, Physics, Mathematics, Biology and Geography we monitor during the period of 2008.1 to 2010.1. Through the analysis of discursive productions, it was evident that the construction of the reference is made by means of the activation and manipulation of information acquired through our perceptual and social experiences. Thus, we confirm the cognitive assumption that the linguistic clues available in the texts of the activities serve as guides towards cognitive domains that activate the process of building reference